FAKTOR YANG BERHUBUNGAN DENGAN LAMANYA PELEPASAN TALI PUSAT DI WILAYAH KERJA PUSKESMAS PAMENANG KABUPATEN MERANGIN - Rosmaria, Rosmaria; Imelda, Imelda; Kusmaryati, Pauline; Rama, Rama (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2025)
Umbilical cord care is a crucial aspect of newborn health, as improper treatment can delay cord separation and increase the risk of infection. This study aimed to determine the factors associated with the duration of umbilical cord separation among newborns in the working area of Pamenang Public Health Center, Merangin Regency. This was a quantitative analytic study using a cross-sectional design, involving 50 mothers with newborns aged 15–30 days selected through total sampling. The variables examined included umbilical cord care practices, cord moisture, and environmental sanitation conditions. Data were collected using structured questionnaires and direct observations, then analyzed using the Chi-Square test with a significance level of 5%. The results showed significant relationships between the duration of cord separation and the three factors studied: cord care practices (p=0.000), cord moisture (p=0.000), and environmental sanitation (p=0.000). It can be concluded that proper cord care, keeping the cord dry, and maintaining a clean environment contribute to faster umbilical cord separation in newborns.